Systematic Review of Surgical Care in the Incarcerated Population: Identifying Knowledge Gaps for Future Research - Totadri Dhimal, MD; Paula Cupertino, PhD; Aqsa Ghaffar, BS; Yue Li, PhD; Xueya Cai, PhD; Cristopher Soto, BS; Megha Ramaswamy, PhD, MPH; Bruce W. Herdman, PhD; Fergal J. Fleming, MD, MPH; Anthony Loria, MD, MSCI (Annals of Surgery Open)
Objective:. This study, examining literature up to December 2023, aims to comprehensively assess surgical care for incarcerated individuals, identifying crucial knowledge gaps for informing future health services research and interventions. Background:. The US prison system detains around 2 million individuals, mainly young, indigent males from ethnic and racial minorities. The constitutional right to healthcare does not protect this population from unique health challenges and disparities. The scarcity of literature on surgical care necessitates a systematic review to stimulate research, improve care quality, and address health issues within this marginalized community. Methods:. A systematic review, pre-registered with the International Prospective Register of Systematic Reviews (CRD42023454782), involved searches in PubMed, Embase, and Web of Science. Original research on surgical care for incarcerated individuals was included, excluding case reports/series (<10 patients), abstracts, and studies involving prisoners of war, plastic surgeries for recidivism reduction, transplants using organs from incarcerated individuals, and nonconsensual surgical sterilization. Results:. Out of 8209 studies screened, 118 met inclusion criteria, with 17 studies from 16 distinct cohorts reporting on surgical care. Predominantly focusing on orthopedic surgeries, supplemented by studies in emergency general, burns, ophthalmology, and kidney transplantation, the review identified delayed hospital presentations, a high incidence of complex cases, and low postoperative follow-up rates. Notable complications, such as nonfusion and postarthroplasty infections, were more prevalent in incarcerated individuals compared with nonincarcerated individuals. Trauma-related mortality rates were similar, despite lower intraabdominal injuries following penetrating abdominal injuries in incarcerated patients. Conclusion:. While some evidence suggests inferior surgical care in incarcerated patients, the limited quality of available studies underscores the urgency of addressing knowledge gaps through future research. This is crucial for patients, clinicians, and policymakers aiming to enhance care quality for a population at risk of surgical complications during incarceration and postrelease.